The Topodiverse City: Urban Form for Subjective Well-Being - Samuelsson, Karl (Frontiers in Built Environment, 2021)
Research is now better than ever able to unveil how urban inhabitants’ movement, behavior and experiences relate to the urban forms in which they take place. Consequently, urban form might increasingly be able to function as a focal point for different strands of research that focus on sustainable urban life, and as a link between research and planning practice through the development of empirically informed design principles. Drawing on literature from urban morphology, complex systems analysis, environmental psychology, and neuroscience, I provide a wide-angle view of how urban form relates to subjective well-being through movement, social and economic activity, experiences and psychological restoration. I propose three principles for urban form that could promote subjective well-being while also mitigating the environmental impact of cities in industrialized societies. The principles revolve around so-called topodiversity, meaning variation across an urban area in spatial conditions that allows subjective well-being to be promoted through several different pathways. The principles together suggest an urban form that I call the topodiverse city. The topodiverse city displays a polycentric structure and is more spatially contained than the sprawling city, yet not as compact as the dense city. I also propose indicators to measure the principles using mostly openly available data and analysis methods, to further research on how urban form can enable urban subjective well-being with low environmental impact.